The Landscape of Androgens in Cushing’s Syndrome - Nowotny, Hanna F.; Braun, Leah; Reisch, Nicole (Experimental and Clinical Endocrinology & Diabetes, 2024)
Hyperandrogenemia in patients with Cushing’s syndrome (CS) presents a diagnostic pitfall due to its rare occurrence and overlapping symptoms with more common conditions like polycystic ovary syndrome (PCOS). This review explores the significance of androgen dysregulation in CS, focusing on both classical and 11-oxygenated androgens. While classical androgens contribute to hyperandrogenism in CS, their levels alone do not fully account for clinical symptoms. Recent research highlights the overlooked role of 11oxC19 androgens, particularly 11OHA4 and 11KT, in driving hyperandrogenic manifestations across all CS subtypes. These adrenal-specific and highly potent androgens offer stable expression throughout the lifespan of a woman, serving as valuable diagnostic biomarkers. Understanding their prominence not only aids in subtype differentiation but also provides insights into the complex nature of androgen dysregulation in CS. Recognizing the diagnostic potential of 11oxC19 androgens promises to refine diagnostic approaches and improve clinical management strategies for patients with CS.
Keywords: Cushing’s syndrome; androgens; 11-oxygenated androgens; hyperandrogenemia